Youths' perceptions of community health workers' delivery of family planning services: a cross-sectional, mixed-methods study in Nakaseke District, Uganda - Robert Kalyesubula; Jessica Mitter Pardo; Stephanie Yeh; Richard Munana; Ivan Weswa; Joseph Adducci; Faith Nassali; Mennen Tefferi; John Mundaka; Sahai Burrowes (BMC, 2021)
Abstract Background High rates of unintended adolescent pregnancy are a significant health problem in Uganda. To improve access to family planning (FP) services, community-based Village Health Teams (VHTs) are widely employed in Uganda to deliver education and services. However, evaluations of FP programs suggest that mainly older, married women use VHT FP services. Methods To better understand youth reluctance to use VHTs, we collected quantitative FP and contraceptive-seeking behavior data from a survey of 250 youths aged 15-25 in randomly selected households in Nakaseke District, which we triangulated with data from 3 focus group discussions (FGDs) (n = 15). Results Most respondents received FP services from the formal health sector, not VHTs. Only half had talked to a VHT, but 65% knew that VHTs provide free FP services, and most (82%) felt comfortable talking to VHTs about FP. The main reasons for discomfort were fear that VHTs would violate privacy (mentioned by 60% of those not comfortable), that VHTs would talk to parents (33%), shyness (mentioned by 42% of those ≤18), and fear of being judged (14%). Concern about side effects was the most common reason for not using FP methods. Survey respondents said having VHTs of the same sex was important, particularly those in the youngest age group (OR = 4.45; 95%CI: 1.24, 16.00) and those who were unmarried (OR = 5.02; 95%CI: 2.42, 10.39). However, FGD participants (who were older than survey respondents on average) often preferred older VHTs of the opposite sex, whom they viewed as more professional and trustworthy. Respondents said the primary deciding factors for using VHTs were whether privacy would be respected, the proximity of care, and the respectfulness of care. Conclusions VHTs are a known source of FP services but not widely used by youth due to privacy and quality of care concerns. VHT messaging and training should increase focus on ensuring privacy, protecting confidentiality, providing respectful care, and addressing concerns about contraceptive side effects. Preferences for VHTs of similar age and sex may be more important for younger adolescents than older youths for whom quality concerns predominate.